Deep Sequencing of Plasma Exosomal microRNA Level in Psoriasis Vulgaris Patients - Chen, Xiu-Min; Yao, Dan-Ni; Wang, Mao-Jie; Wu, Xiao-Dong; Deng, Jing-Wen; Deng, Hao; Huang, Run-Yue; Lu, Chuan-Jian (Frontiers in Medicine, 2022)
Psoriasis is a chronic skin disease affecting 1% to 3% of the world population. Psoriasis vulgaris (PV) is the most common form of psoriasis. PV patients suffer from inflamed, pruritic and painful lesions for years (even a lifetime). However, conventional drugs for PV are costly. Considering the need for long-term treatment of PV, it is urgent to discover novel biomarkers and therapeutic targets. Serum exosomal miRNAs have been identified as the reliable biomarkers and therapy targets of human diseases. Here, we described the levels of serum exosomal miRNAs in PV patients and analyzed the functional features of differently expressed miRNAs and their potential target genes for the first time. We identified 1182 miRNAs including 336 novel miRNAs and 246 differently expressed miRNAs in serum exosomes of healthy people and PV patients. Furthermore, the functional analysis found differently expressed miRNA-regulated target genes enriched for specific GO terms including primary metabolic process, cellular metabolic process, metabolic process, organic substance metabolic process, and KEGG pathway containing cellular processes, human diseases, metabolic pathways, metabolism and organismal systems. In addition, we found that some predicted target genes of differentially expressed miRNAs, such as CREB1, RUNX2, EGFR, are both involved in inflammatory response and metabolism. In summary, our study identifies many candidate miRNAs involved in PV, which could provide potential biomarkers for diagnosis of PV and targets for clinical therapies against PV.